Leaf traits of Calophyllum inophyllum L. (calophyllaceae) in different locations suggest suitability for planting outside of natural habitat - Calibo, Ma. Kristina T.; Tinio, Crusty E.; Combalicer, Marilyn S.; Maldia, Lerma S.J (Vol.150, No.4 (August 2021), pages 643-656.)
"Calophyllum inophyllum L. (bitaog), a native tree species in the Philippines that can be found growing in different locations (urban, coastal, and forest areas) with varying climatic conditions, were studied to compare the morphological and anatomical characters in relation to climatic factors. Nine leaf morphological characters (arrangement, apex, base, margin, shape, venation, texture, length, and width) were observed. The thicknesses of the epidermis, vascular tissues, and mesophyll were measured. One-way analysis of variance (ANOVA) was used to show significant differences in morphological and anatomical characters among locations"-title page.